Research progress and perspective on lithium/sodium metal anodes for next-generation rechargeable batteries - Patrike, Apurva; Yadav, Poonam; Shelke, Vilas; Shelke, Manjusha (ChemSusChem, 2022)
With the development of consumer electronic devices and electric vehicles, lithium-ion batteries (LIBs) are vital components for high energy storage with great impact on our modern life. However, LIBs still cannot meet all the essential demands of rapidly growing new industries. In pursuance of higher energy requirement, metal batteries (MBs) are the next-generation high-energy-density devices. Li/Na metals are considered as an ideal anode for high-energy batteries due to extremely high theoretical specific capacity (3860 and 1165 mAh g(-1) for Li and Na, respectively) and low electrochemical potential (-3.04 V for Li and -2.71 V for Na vs. standard hydrogen electrode). Unfortunately, uncontrolled dendrite growth, high reactivity, and infinite volume change induce severe safety concerns and poor cycle efficiency during their application. Consequently, MBs are far from commercialization stage. This Review represents a comprehensive overview of failure mechanism of lithium/sodium metal anode and its progress for rechargeable batteries through (i) electrolyte optimization, (ii) artificial solid-electrolyte interphase (SEI) layer formation, and (iii) nanoengineering at materials level in current collector, anode, and host. The challenges in current MBs research and potential applications of lithium/sodium metal anodes are also outlined and summarized.
Keywords: anode; Batteries; dendrite growth; Electrolytes; Energy storage

Role of 2D material families in energy harvesting: an editorial overview - Raghavan, Prasanth; Ahn, Jou-Hyeon; Shelke, Manjusha (Journal of Materials Research, 2022)
The ever increasing proportion of an energy consuming society and the boost in industrialization accelerated the depletion of fossil fuel based energy sources at an alarming rate. This emphasizes the necessity of sustainable energy generation and storage to meet the daily energy demands. But, these alternative renewable energy sources like solar and wind power are intermittent and highly depend on weather, place and individuals. This creates the inevitability of suitable energy storage devices like batteries and supercapacitors. The interfacing of energy storing devices is required to maintain the supply chain equilibrium, power efficiency, regulate power fluctuations and reduce pollution. Besides, the boom in electric mobility and consumer electronics also require uninterrupted power supply. Hence, in the upcoming years the energy storing devices play a vital role in addressing the energy crisis. Innovations in new materials and technologies will be the core area of research and development in the coming future. 2D materials like graphene,transition metal carbides and nitrides (MXenes), transition metal borides (MBenes) and so on are the new class of materials among them MXenes are getting more attention in energy storage owing to its exceptional properties.